Prognostic value of H‐index in patients surgically treated for squamous cell carcinoma of the larynx. Issue 4 (23rd June 2021) - Boscolo‐Rizzo, Paolo; Zanelli, Enrico; Giudici, Fabiola; Boscolo‐Nata, Francesca; Cristalli, Giovanni; Deganello, Alberto; Tomasoni, Michele; Piazza, Cesare; Bossi, Paolo; Spinato, Giacomo; Menegaldo, Anna; Emanuelli, Enzo; et al.
Abstract: Objective: Recently, a novel host‐related index, the Host‐index (H‐index), including both inflammatory and nutritional markers, has been described and observed to stratify prognosis in patients with squamous cell carcinoma (SCC) of the oral cavity more accurately than other host‐related indexes This study aimed to investigate the prognostic performance of the H‐index using pretreatment blood tests in patients receiving up‐front surgery for SCC of the larynx. Methods: This retrospective observational study included a multicenter series of consecutive patients with SCC of the larynx diagnosed between 1 January 2009 and 31 July 2018, whose pretreatment blood tests were available and included the parameters necessary for the calculation of neutrophil to lymphocyte ratio (NLR) and the H‐index. Their association with disease‐free survival (DFS) and overall survival (OS) was measured. Results: A total of 231 patients were eligible for the present analysis (median [range] age, 68 [37‐96] years; 191 [82.7%] men). The median follow‐up was 73 months. In multivariable Cox proportional hazards regression models, increasing age (adjusted hazard ratio [aHR], 1.07 per year; 95% CI, 1.04‐1.09), advanced pT stage (aHR = 1.71 95% CI: 1.07‐2.71), and having close or positive surgical margins (aHR = 2.01; 95% CI: 1.21‐3.33) were significantly associated with poor OS. Among blood parameters, a higher neutrophil count was a strong predictor of both worse DFS (aHR for recurrence/death = 2.34; 95% CI: 1.24‐4.40) and OS (aHR for death = 2.67; 95% CI: 1.51‐4.71). Among inflammatory blood indexes, while NLR was not significantly associated with DFS or OS, patients with H‐index ≥8.37 showed a higher aHR for both recurrence/death (2.82; 95% CI: 1.65‐4.79) and death (2.22; 95% CI: 1.26‐3.89). Conclusion: In conclusion, the present study confirms the prognostic value of pretreatment H‐index, an easily measurable inflammatory and nutritional index, in patients with SCC of the larynx. Level of Evidence: III